The Use of Random Forests to Identify Brain Regions on Amyloid and FDG PET Associated With MoCA Score. (June 2020) - Zukotynski, Katherine; Gaudet, Vincent; Kuo, Phillip H.; Adamo, Sabrina; Goubran, Maged; Scott, Christopher J.M.; Bocti, Christian; Borrie, Michael; Chertkow, Howard; Frayne, Richard; Hsiung, Robin; Laforce, Robert; et al.
Abstract : Purpose: The aim of this study was to evaluate random forests (RFs) to identify ROIs on 18 F-florbetapir and 18 F-FDG PET associated with Montreal Cognitive Assessment (MoCA) score. Materials and Methods: Fifty-seven subjects with significant white matter disease presenting with either transient ischemic attack/lacunar stroke or mild cognitive impairment from early Alzheimer disease, enrolled in a multicenter prospective observational trial, had MoCA and 18 F-florbetapir PET; 55 had 18 F-FDG PET. Scans were processed using the MINC toolkit to generate SUV ratios, normalized to cerebellar gray matter ( 18 F-florbetapir PET), or pons ( 18 F-FDG PET). SUV ratio data and MoCA score were used for supervised training of RFs programmed in MATLAB. Results: 18 F-Florbetapir PETs were randomly divided into 40 training and 17 testing scans; 100 RFs of 1000 trees, constructed from a random subset of 16 training scans and 20 ROIs, identified ROIs associated with MoCA score: right posterior cingulate gyrus, right anterior cingulate gyrus, left precuneus, left posterior cingulate gyrus, and right precuneus. Amyloid increased with decreasing MoCA score. 18 F-FDG PETs were randomly divided into 40 training and 15 testing scans; 100 RFs of 1000 trees, each tree constructed from a random subset of 16 training scans and 20 ROIs, identified ROIs associated with MoCA score: left fusiform gyrus, left precuneus, left posterior cingulate gyrus, right precuneus, and left middle orbitofrontal gyrus. 18 F-FDG decreased with decreasing MoCA score. Conclusions: Random forests help pinpoint clinically relevant ROIs associated with MoCA score; amyloid increased and 18 F-FDG decreased with decreasing MoCA score, most significantly in the posterior cingulate gyrus.